Ce qui fait et ceux qui font la professionnalisation en IUT - Stéphanie Tralongo
In common literature, the French 'Instituts Universitaires de Technologie' (IUT) are generally presented as a specific part of the University: they deal with vocational education training at a tertiary level. This article aims to explore this common representation. In fact, what really is prfessionnalization practices in IUTs? Who defines and organizes it? The research is based on the bernstannian theoretical approach (sociology of Curriculum). The purpose is to adopt a socio-historian point of view about the vocationalism and professionalization in Higher Education by mixing two types of approaches: a corpus constituted by different kinds of texts (laws, IUT's literature, etc.) and an ethnography. The study demonstrates that vocational definition founded in this field links institutional organization and the curriculum. More precisely, the expected practices mean a lot of ways to get closer academic and labor market worlds.